Hydrogen production from the fermentation of pineapple agroindustrial wastes - Montoya-Pérez, Luisa (2017)
Hydrogen production from the fermentation of pineapple core wastes was studied using pretreated sludge from a local UASB wastewater treatment plant as inoculum. Applying a 23 factorial design, the effects of initial substrate concentration, initial fermentation medium pH, and type of nutrient formulation on H2 production were studied. The best results were obtained at pH of 5,5, with a substrate concentration of 5 (g glucose)/L, and using a nutrient formulation based on magnesium, iron, zinc, and sodium. Then, utilizing the previous operating conditions, the fermentation was scaled up to a 5 L bioreactor and a maximum yield of 1,541 (mol H2)/(mol glucose) was achieved. This hydrogen yield is comparable with others reported in the literature when glucose was used as substrate. These results suggest that pineapple core wastes could be used as a renewable source for hydrogen production.